155k views
5 votes
Expand.

If necessary, combine like terms.
(
3
x
+
7
)
(
3
x

7
)
=
(3x+7)(3x−7)=left parenthesis, 3, x, plus, 7, right parenthesis, left parenthesis, 3, x, minus, 7, right parenthesis, equals

User Suzana
by
5.1k points

2 Answers

2 votes

Answer:

9x^2-49

Explanation:

did it on khan academy
hope this helps!

User Vishal Khatri
by
5.4k points
1 vote

Answer: 9x^2-49

Step-by-step explanation: using pattern (a+b)(a-b)=a^2-b^2

(3x+7)(3x-7)=(3x)^2-7^2

=9x^2-49

User JChao
by
4.6k points